2021
DOI: 10.3390/mi12030261
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Artificial 3-Dimensional Ovarian Follicle Culture System Using a Microfluidic System

Abstract: We hypothesized that the creation of a 3-dimensional ovarian follicle, with embedded granulosa and theca cells, would better mimic the environment necessary to support early oocytes, both structurally and hormonally. Using a microfluidic system with controlled flow rates, 3-dimensional two-layer (core and shell) capsules were created. The core consists of murine granulosa cells in 0.8 mg/mL collagen + 0.05% alginate, while the shell is composed of murine theca cells suspended in 2% alginate. Somatic cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Interestingly, the results obtained indicated that the relative expression levels of each specific gene vs. all the other genes considered was maintained for all of the engrafting period. Although further studies are needed to better elucidate this aspect, it is tempting to speculate that, different from what was reported for 2D culture systems where a poor correlation with in vivo conditions was detected [40,41], the decellularized ECM-based scaffold niche may provide repopulating cells with inputs that preserve the transcription regulatory mechanisms at work in their native tissue, offering an adequate 3D microenvironment driving repopulating cells. This hypothesis found further support in the results obtained when ECM-based scaffolds were repopulated with epigenetically erased cells obtained through epigenetic erasing [30][31][32][33][34][35][36][37][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, the results obtained indicated that the relative expression levels of each specific gene vs. all the other genes considered was maintained for all of the engrafting period. Although further studies are needed to better elucidate this aspect, it is tempting to speculate that, different from what was reported for 2D culture systems where a poor correlation with in vivo conditions was detected [40,41], the decellularized ECM-based scaffold niche may provide repopulating cells with inputs that preserve the transcription regulatory mechanisms at work in their native tissue, offering an adequate 3D microenvironment driving repopulating cells. This hypothesis found further support in the results obtained when ECM-based scaffolds were repopulated with epigenetically erased cells obtained through epigenetic erasing [30][31][32][33][34][35][36][37][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies have demonstrated the efficacy of microfluidic chips in the culturing of single human preantral follicles, with results comparable to those obtained through traditional methods [ 124 ], which is shown in Fig. 2 c Furthermore, the application of this technology in constructing double-layer follicles composed of mouse granulosa cells has yielded promising results, with the resulting follicles exhibiting endocrine function such as the production of estradiol, progesterone, and androstenedione [ 125 ]. Microfluidic chips also have the potential to be integrated with other human organ chips to construct an integrated human body model, so as to better study the endocrine, immune, metabolic and other factors involved in follicular development [ 123 ], as shown in Fig.…”
Section: Ovarian Research Using Microfluidic Systemsmentioning
confidence: 84%
“…When integrating with microfluidic chips, the decellularization and recellularization manipulation can be reproduced directly in the devices or used as medium to fill the chips ( Hong et al , 2017 ; Palikuqi et al , 2020 ; Bhatt et al , 2022 ). The latter provides a dynamic stimulus to the cumulus cell–oocyte complex or denuded oocytes, which improves the outcomes of oocyte maturation and IVF ( Nagashima et al , 2018 ; Podwin et al , 2020 ; Healy et al , 2021 ; Sadeghzadeh Oskouei et al , 2021 ). Altogether, the integration of these advanced culture systems will facilitate the development of ovarian regeneration and drug-testing models.…”
Section: Discussionmentioning
confidence: 99%